A high-quality chromosome-scale assembly of the centipedegrass [Eremochloa ophiuroides (Munro) Hack.] genome provides insights into chromosomal structural evolution and prostrate growth habit. (1st September 2021) - Wang, Jingjing; Zi, Hailing; Wang, Rui; Liu, Jianxiu; Wang, Haoran; Chen, Rongrong; Li, Ling; Guo, Hailin; Chen, Jingbo; Li, Jianjian; Zong, Junqin
Abstract: Centipedegrass [ Eremochloa ophiuroides (Munro) Hack.], a member of the Panicoideae subfamily, is one of the most important warm-season turfgrasses originating from China. This grass has an extremely developed prostrate growth habit and has been widely used in transitional and warm climatic regions. To better understand the genetic basis of important biological characteristics, such as prostrate growth and seed yield, in warm-season turfgrasses, we present a high-quality reference genome for centipedegrass and use PacBio, BioNano, and Hi-C technologies to anchor the 867.43 Mb genome assembly into nine pseudochromosomes, with a scaffold N50 of 86.05 Mb and 36, 572 annotated genes. Centipedegrass was most closely related to sorghum and diverged from their common ancestor ~16.8 Mya. We detected a novel chromosome reshuffling event in centipedegrass, namely, the nest chromosome fusion event in which fusion of chromosomes 8 and 10 of sorghum into chromosome 3 of centipedegrass likely occurred after the divergence of centipedegrass from sorghum. The typical prostrate growth trait in centipedegrass may be linked to the expansion of candidate PROSTRATE GROWTH 1 ( PROG1 ) genes on chromosome 2. Two orthologous genes of OsPROG1, EoPROG1, and EoPROG2, were confirmed to increase the stem number and decrease the stem angle in Arabidopsis . Collectively, our assembled reference genome of centipedegrass offers new knowledge and resources to dissect the genome evolution of Panicoideae and accelerate genome-assisted breeding and improvement of plant architecture in turf plants.